Game change Obama and the Clintons, McCain and Palin, and the race of a lifetime - Heilemann, John 1966-; Halperin, Mark (New York Harper, 2010)
From two of the best political reporters in the country comes the gripping inside story of the historic 2008 presidential election
Her time -- The alternative -- The ground beneath her feat -- Getting to yes -- The inevitables -- Barack in a box -- "They loooooove me!" -- The turning point -- The fun part -- Two for the price of one -- Fear and loathing in the lizard's thicket -- Pulling away and falling apart -- Obama agonistes -- The bitter end game -- The Maverick and his meltdown -- Running unopposed -- Slipping nooses, slaying demons -- Paris and Berlin -- The Mile-High Club -- Sarahcuda -- September Surprise -- Seconds in command -- The finish line -- Together at last
Includes index
1
Keywords: Clinton, Hillary Rodham; McCain, John -- 1936-2018; Obama, Barack; Palin, Sarah -- 1964-; Elections -- United States -- History -- 21st century; Political campaigns -- United States -- History -- 21st century; Presidents -- United States -- Election -- 2008; United States -- Politics and government -- 2001-2009